Work–Life Balance and Perceived Digital Recruitment Effectiveness among Generation Z: A Sequential Mediation Model of Recruitment Experience and Job Search Self-Efficacy - Yayat Sudrajat; Nausheen Shakeel; Udin Zaenudin; Kania Laelawati; Dodi Siswanto (Business and Applied Management Journal, 2026)
Digital recruitment has changed how Generation Z evaluates prospective employers, shifting attention from job availability toward platform-based experiences, process transparency, and alignment with work values. This study examines the effect of work–life balance on perceived digital recruitment effectiveness through digital recruitment experience and job search self-efficacy. A quantitative cross-sectional survey was conducted with 301 Generation Z job portal users in Jakarta, Bandung, and Surabaya selected through purposive sampling. Data were analyzed using PLS-SEM with SmartPLS 4.0. The results show that work–life balance does not directly affect perceived digital recruitment effectiveness (β = −0.062; p = 0.101). In contrast, digital recruitment experience (β = 0.678; p < 0.001) and job search self-efficacy (β = 0.382; p < 0.001) have positive and significant effects. The indirect effect through digital recruitment experience is also significant (β = 0.607; p < 0.001), as is the sequential mediation through digital recruitment experience and job search self-efficacy (β = 0.206; p < 0.001). Organizations and job portal providers should clarify vacancy and selection information, accelerate HR responses, provide transparent application-status updates, and minimize technical barriers. This study provides practical implications for organizations seeking to optimize digital recruitment strategies by enhancing candidate experiences, transparency, and confidence throughout the recruitment process.